Voltage stability monitoring and improvement in a renewable energy dominated deregulated power system: A review - Karuppasamy Anthony; Venkadesan Arunachalam (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
Recently, there has been a significant focus on voltage stability in power systems due to the difference between power generation and demand. Maintaining voltage stability poses challenges in power system planning and security assessment. Elements such as the growing demand for electricity, depletion of fossil fuels, environmental concerns, and infrastructure reliability have prompted power utility corporations to incorporate renewable sources into traditional power systems. However, there are issues with system voltage stability when non-dispatchable renewable energies like solar and wind energy are integrated into the current transmission and distribution networks. This paper comprehensively studies essential problems related to voltage instability in renewable-integrated systems, employing traditional and machine-learning techniques for voltage stability assessment. The paper also explores using different compensating devices, for example, fixed capacitors, flexible AC transmission systems (FACTS), and energy storage systems, to enhance voltage stability in distribution and transmission networks. Additionally, it examines locational marginal pricing in a deregulated environment. The findings and outcomes of this review offer valuable insights into voltage stability analysis in renewable integrated power systems and highlight upcoming investigation directions in the power system stability field.